2015
DOI: 10.1371/journal.pone.0127441
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in MCF-7 Cells via Oxidative Stress Generation, Mitochondria-Dependent and Caspase-Independent Pathway by Ethyl Acetate Extract of Dillenia suffruticosa and Its Chemical Profile

Abstract: Dillenia suffruticosa, which is locally known as Simpoh air, has been traditionally used to treat cancerous growth. The ethyl acetate extract of D. suffruticosa (EADs) has been shown to induce apoptosis in MCF-7 breast cancer cells in our previous study. The present study aimed to elucidate the molecular mechanisms involved in EADs-induced apoptosis and to identify the major compounds in the extract. EADs was found to promote oxidative stress in MCF-7 cells that led to cell death because the pre-treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 70 publications
(67 reference statements)
3
42
0
3
Order By: Relevance
“…To rule out the possibility that NAC could be involved in covalent interactions with WA [8], both the cells were treated with another ROS inhibitor, ascorbic acid (100 μM)[23] for 6h, followed by WA treatment and checked cytoplasmic vacuolation, percentage of cell survival and the levels of proliferation associated factorand ER-stress related factors.Phase contrast microscopic images (Fig 4G) showed that treatment with WA for 24 h induced extensive cytoplasmic vacuolation, which was abrogated by co-treatment with ascorbic acid, that corresponds to the earlier observations using NAC. Treatment with ascorbic acid also predominantly inhibited WA-mediated cellular death (Fig 4H), down regulation of PCNA and Alix, alongwith marked elevation ofER-stress related protein GRP-78 (Bip) (Fig 4I).…”
Section: Resultsmentioning
confidence: 99%
“…To rule out the possibility that NAC could be involved in covalent interactions with WA [8], both the cells were treated with another ROS inhibitor, ascorbic acid (100 μM)[23] for 6h, followed by WA treatment and checked cytoplasmic vacuolation, percentage of cell survival and the levels of proliferation associated factorand ER-stress related factors.Phase contrast microscopic images (Fig 4G) showed that treatment with WA for 24 h induced extensive cytoplasmic vacuolation, which was abrogated by co-treatment with ascorbic acid, that corresponds to the earlier observations using NAC. Treatment with ascorbic acid also predominantly inhibited WA-mediated cellular death (Fig 4H), down regulation of PCNA and Alix, alongwith marked elevation ofER-stress related protein GRP-78 (Bip) (Fig 4I).…”
Section: Resultsmentioning
confidence: 99%
“…In response to intracellular and extracellular stress, p53 is activated and serves as a transcription factor that orchestrates various targets, which in turn modulate multitude of cellular processes such as DNA repair, cell cycle arrest and apoptosis (28,29). It is reported that p53-inducible pro-apoptotic genes trigger apoptosis through both the extrinsic and the intrinsic apoptotic molecular pathways (30).…”
Section: Discussionmentioning
confidence: 99%
“…This compound has been reported to have in vitro cytotoxic activity against MCF-7 and MDA-MB-231 cells [21]. In alkaloid class, only (-)-auranamide, isolated from B.nantoensis exhibited the higher chemPLP score of -108.512.…”
Section: Resultsmentioning
confidence: 99%